A national approach for the use of simulation to educate and train the NHS workforce: the First National Clinical Skills Strategy. Issue 4 (November 2015) - Ker, Jean; Cachia, Philip; Beasant, Beverley
Introduction: There have been a number of drivers for the use of simulation in healthcare education for the NHS workforce. The development of an accessible and efficient national approach to its implementation has been challenging. Methods: An action research approach was used to develop a national strategy using several data inputs. Results: From sampling across practitioners and territorial health boards geographical and professional groups, access was the main challenge to the use of simulation. Conclusion: Four priority areas were identified, which formed the basis of the national strategy Partnership for Care, which included a mobile unit, a managed educational network, a programme board and an alliance of stakeholders.